Which Schools and Pupils Respond to Educational Achievement Surveys? A Focus on the English PISA Sample - Sylke V. Schnepf; Gabriele B. Durrant; John Micklewright (Institute for the Study of Labor (IZA), 2014)
Using logistic and multilevel logistic modelling we examine non-response at the school and pupil level to the important educational achievement survey Programme for International Student Assessment (PISA) for England. The analysis exploits unusually rich auxiliary information on all schools and pupils sampled for PISA whether responding or not, including data from two large-scale administrative sources on pupils' results in national public exams, which correlate highly with the PISA target variable. Results show that characteristics associated with non-response differ between the school and pupil levels. The findings have important implications for the survey design of education data.
Keywords: I21; C83; 330; Programme for International Student Assessment (PISA); survey design; data linkage; non-response; educational achievement survey